Incorporating Flexibility into Stiffness: Self‐Grown Carbon Nanotubes in Melamine Sponges Enable A Lithium‐Metal‐Anode Capacity of 15 mA h cm−2 Cyclable at 15 mA cm−2. Issue 7 (14th December 2018) - Xie, Jian; Ye, Jianglin; Pan, Fei; Sun, Xuemei; Ni, Kun; Yuan, Hong; Wang, Xiangyang; Shu, Na; Chen, Chunhua; Zhu, Yanwu
Abstract: Although with an extremely high theoretical capacity (3860 mA h g −1 ), the lithium (Li) metal anodes reported so far typically possess capacities of ≤5 mA h cm −2 and cyclable at currents of ≤5 mA cm −2 . In this work, a hierarchal carbon scaffold is designed with the self‐growth of carbon nanotubes (CNTs) in nickel‐decorated melamine sponges via thermal annealing. It is found that the nitrogen‐doped carbon obtained from the melamine sponge, coupled with CNTs, provides an overall strong yet internally flexible host which enables an areal capacity of up to 15 mA h cm −2 cyclable at a charging/discharging current of 15 mA cm −2 as Li metal anodes. Characterizations show that the highly conductive yet uniformly distributed CNTs effectively suppress the local current density, leading to more uniform Li nucleation in Li plating. The flexible CNTs in the stiff scaffold enhance the tolerance to the stress caused by the intrinsic volume variation in Li plating/striping, resulting in the stable cycling performance at high currents. This study provides a potentially scalable and cost‐effective strategy for preparation of high‐performance Li‐metal anodes. Abstract : Carbon‐nanotube‐decorated melamine carbon (CNTs‐MC) with an ultrahigh capacity of 15 mA h cm −2 at 15 mA cm −2 as a lithium‐metal anode is obtained by via simple annealing. Notably, the flexible CNTs improve the tolerance to strains and reduce the local current. At the same time, the stiff MC assures excellent stability, resulting in a highly stable solid electrolyte interphase and superior cycling performance.